2013
DOI: 10.1021/es401615y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Toxic Effects of Municipal Wastewater Effluent on Mice Using Omic Approaches

Abstract: Municipal wastewater effluents (MWWE) contain a lot of trace organic pollutants, which will be a threat to environmental health. However, little information is available for the mixed toxicity of MWWE on mammals. In the present study, male mice were exposed to MWWE for 90 days, and then, histopathology and clinical biochemistry determination and transcriptomic and metabolomic profiling were conducted. The results showed that MWWE exposure resulted in injuries in liver and kidney. Combined transcriptomic and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…NMR spectra were processed (phase correction, baseline correction and ppm shift correction using trisilylpropionic acid [TSP] or tetramethylsilane [TMS]) and analyzed (GSD, Global Spectral Deconvolution) using MestReNova v6.1.0–6224 software. Metabolite resonances were identified using both Chenomx NMR Suite 8.02 and published literature 31 32 33 . NMR spectra and assigned metabolites are presented in Figure S1 , Figure S2 and Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…NMR spectra were processed (phase correction, baseline correction and ppm shift correction using trisilylpropionic acid [TSP] or tetramethylsilane [TMS]) and analyzed (GSD, Global Spectral Deconvolution) using MestReNova v6.1.0–6224 software. Metabolite resonances were identified using both Chenomx NMR Suite 8.02 and published literature 31 32 33 . NMR spectra and assigned metabolites are presented in Figure S1 , Figure S2 and Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, the combinations of gas chromatography-quadrupole time of flight mass spectrometry (GC-Q-TOF/MS) and liquid chromatography-quadrupole time of flight mass spectrometry (LC-Q-TOF/MS) have been applied successfully in numerous metabolomics studies to achieve more sensitive and accurate metabolic profiling and screening of biomarkers [15]. For instance, Zhang et al employed NMR-based metabolomics to study the toxic effects of municipal wastewater effluent in mice and found that municipal wastewater effluent induced amino acid, nucleotide, lipid, and energy metabolism perturbations, which result in hepatotoxicity and nephrotoxicity in mice [16]. Xu et al adopted 1 H-NMR based metabolomics to study the toxic effects of butachlor on gold fish and found that metabolic pathways related to oxidative stress, energy metabolism, amino acids metabolism, and neurotransmitter balance were significantly perturbed after butachlor exposure [17].…”
Section: Introductionmentioning
confidence: 99%
“…These advantages prompted the use of toxicogenomics to test the effect of single molecules or simple chemical mixtures [ 8 , 9 ]. The objectives of transcriptomics in environmental studies (ecotoxicogenomics) are the accomplishment of classical toxicological and new molecular endpoints in the identification of exposure-related alterations, and proper consideration of the complex nature of anthropogenic pollution and bioaccumulation events [ 10 17 ]. Besides environments are frequently contaminated with multiple classes of compounds, only a limited number of toxicological studies have recently addressed this problem by using omics approaches to fish species, in environmental field [ 11 , 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the integration of toxicogenomics data from different models is pivotal to validate deregulated patterns, to challenge the low signal to noise ratio and to predict potential risks for human health [ 23 , 24 ]. Mouse and zebrafish studies indicate that gene expression profile approaches are successful in identifying chemical-specific patterns of altered gene expression [ 2 , 25 27 ]; for this reason, and for their genetics and biology, these models are widely accepted by the scientific community for environmental toxicology studies [ 10 , 28 ].…”
Section: Introductionmentioning
confidence: 99%